Pendapatan Keuangan Dan Pengetahuan Keuangan Terhadap Perilaku Keuangan Karyawan Di Lingkungan PT. CS2 Pola Sehat Pasuruan - Ahmad Wanto Baihaki; Nurhidayah Nurhidayah; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this study was to analyze and test the effect of Financial Income and Financial Knowledge on the Financial Behavior of employees. This study uses an explanatory research approach. The location of this research was conducted at the company PT CS 2 Healthy Patterns Pasuruan. This research will be conducted in December October 2021 until it is completed. The population in this study were employees of PT CS 2 Healthy Pattern Pasuruan. Sampling was carried out based on the census method, with a total sample of 33 samples. The results of the study stated that Financial Income and Financial Knowledge had a positive and significant effect on Financial Behavior, Financial Income had a positive and significant effect on Financial Behavior and Financial Knowledge had a positive and significant effect on Financial Behavior. Keywords: Financial Behavior, Financial Income and Financial Knowledge